2007
DOI: 10.1177/0149206307309265
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Justice and Organizational Citizenship Behavior: A Mediated Multifoci Model †

Abstract: This research explores the differential effects of multifoci organizational justice perceptions on organizational citizenship behavior. Based on data collected from 217 employee—supervisor dyads, our findings clarify the bi-focal nature of distributive and procedural justice, illuminate the mono-focus of interpersonal justice, and support the premise that justice investments yield exponential behavioral responses that are sometimes mediated by the quality of the employee— supervisor relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
196
1
21

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(226 citation statements)
references
References 38 publications
8
196
1
21
Order By: Relevance
“…Organ (1997) suggested that organizational citizenship behavior enhances the social and psychological context that supports task performance, and thus positively and indirectly contributes to organizational effectiveness. It was shown that employees meaningfully discriminate between the different targets when directing their citizenship behaviors (e.g., Karriker & Williams, 2009;Williams & Anderson, 1991). Hence, citizenship research often relies on the distinction between organizationally and interpersonally oriented citizenship behaviors (Williams & Anderson, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Organ (1997) suggested that organizational citizenship behavior enhances the social and psychological context that supports task performance, and thus positively and indirectly contributes to organizational effectiveness. It was shown that employees meaningfully discriminate between the different targets when directing their citizenship behaviors (e.g., Karriker & Williams, 2009;Williams & Anderson, 1991). Hence, citizenship research often relies on the distinction between organizationally and interpersonally oriented citizenship behaviors (Williams & Anderson, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Existe evidencia de que la percepción de justicia organizacional es la variable que, en mayor medida, predice los comportamientos de ciudadanía organizacional Hernández & Yáber, 2009;Karriker & Williams, 2009;Moorman, 1991;Organ et al, 2005).…”
Section: ¿Qué Son Los Comportamientos De Ciudadanía Organizacional?unclassified
“…Segundo, se pone en evidencia que la justicia organizacional puede ser considerada un recurso organizacional valioso que promueve el engagement en el trabajo. Tercero, también queda demostrado en este estudio que la justicia organizacional y los CCO están positivamente y significativamente relacionados, lo que coincide con hallazgos previos de otras investigaciones (Cohen-Charash & Spector, 2001;DeConinck, 2010;Karriker & Williams, 2009;Moorman, 1991;. Al mismo tiempo queda evidenciado que el engagement en el trabajo media en su totalidad la relación que existe en la justicia organizacional y los CCO.…”
Section: Implicaciones Teóricasunclassified
“…Hence, supply chain members' perceptions of (1) organisational support (e.g. support within the supply chain) (Karriker and Williams, 2009), (2) reciprocal behaviours (e.g. Graham and Organ, 1993), and (3) a sense of fairness (e.g.…”
Section: Corporate Social Performance (Csp)mentioning
confidence: 99%